Biochar addition can reduce NOx gas emissions from a calcareous soil. Issue 1 (1st January 2019) - Wang, Bing; Lee, Xinqing; Theng, Benny K. G.; Zhang, Like; Cheng, Hongguang; Cheng, Jianzhong; Lyu, Wenqiang
ABSTRACT: The effect of biochar (BC) addition on NOx gas emissions was investigated from a calcareous soil. Application rates of zero (BC0), 1 (BC1), 2 (BC2), 5 (BC5), and 10 (BC10) percent weight/weight were used. The NOx emission flux was measured in a dynamic flux chamber. The flux was generally higher in BC0 than in the amended plots. The total NOx emission from BC1, BC2, BC5, and BC10 fell by 50.3, 75.3, 80.4, and 79.6%, respectively, relative to BC0. The emission flux from the BC5 showed a minimum average of 21.1 ± 13.5 μg N/(m 2 h) for NO, −0.81 ± 1.31 μg N/(m 2 h) for NO2, and 20.6 ± 13.8 μg N/(m 2 h) for NO x . By comparison, the measured maximum average emission flux from the BC0 was 107.2 ± 30.98 μg N/(m 2 h) for NO, −2.31 ± 2.56 μg N/(m 2 h) for NO2, and 105.3 ± 45.3 μg N/(m 2 h) for NO x . The results indicate that biochar amendment can potentially reduce NOx emissions.